Resilience and Intercultural Interactions of Italian Erasmus Students: The Relation with Cultural Intelligence - Dolce, Valentina; Ghislieri, Chiara (Journal of International Students, 2021)
Cultural Intelligence (CQ) has been examined in the literature, nevertheless yet few studies have combined situational and personal aspects to enhance the comprehension of this construct, and none have considered resilience. Therefore, this study aims to investigate the role of international Erasmus students’ resilience, the length of the experience and the intercultural interactions of Italian Erasmus students in the relationship with CQ. Data were collected from 791 outgoing Italian Erasmus students using a self-report questionnaire. The findings suggested the existence of a significant relationship between resilience and all dimensions of CQ, showing, with the exception of the behavioural dimension, large betas. Forming friendships with international students was positively and moderately related to motivational and metacognitive CQ. Establishing relationships with locals was only positively and weakly related to cognitive CQ. The time of sojourn was only positively weakly associated with the metacognitive CQ. Developments in international academic mobility policies are discussed.